Hybrid nanoparticulate system of Fluvastatin loaded phospholipid, alpha lipoic acid and melittin for the management of colon cancer - Alfaleh, Mohamed A.; Fahmy, Omar; Abourehab, Mohammed A. S.; Fahmy, Usama A.; Alharbi, Awaad S.; Alhakamy, Nabil A. (Nature Publishing Group, 2022)
As a hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, Fluvastatin (FLV) is used for reducing low-density lipoprotein (LDL) cholesterol as well as to prevent cardiovascular problems. FLV showed cell line cytotoxicity and antitumor effect. Melittin (MEL) exhibits antineoplastic activity and is known to be promising as a therapeutic option for cancer patients. The aim of this work was to investigate the combination of FLV with MEL loaded hybrid formula of phospholipid (PL) with alpha lipoic acid (ALA) nanoparticles to maximize anticancer tendencies. This study examines the optimization of the prepared formulation in order to minimize nanoparticles size and maximize zeta potential to potentiate cytotoxic potentialities in colon cancer cells (Caco2), cell viability, cell cycle analysis and annexin V were tested. In addition to biological markers as P53, Bax, bcl2 and Caspase 3 evaluation The combination involving FLV PL ALA MEL showed enhanced cytotoxic potentiality (IC50 = 9.242 ± 0.35 µg/mL), about twofold lower, compared to the raw FLV (IC50 = 21.74 ± 0.82 µg/mL). According to studies analyzing cell cycle, optimized FLV PL ALA MEL was found to inhibit Caco2 colon cancer cells more significantly than other therapeutic treatments, wherein a higher number of cells were found to accumulate over G2/M and pre-G1 phases, whereas G0/G1/S phases witnessed the accumulation of a lower number of cells. The optimized formulation may pave the way for a novel and more efficacious treatment for colon cancer.